2014
DOI: 10.5539/ass.v10n9p213
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Relationship between Corporate Governance and Bank Performance – An Empirical Study on Vietnamese Banks

Abstract: The paper examines the impact of corporate governance on performance of Vietnamese banks. The Corporate Governance Index has been used to evaluate corporate governance of Vietnamese banks in the period of 2010-2012. The return on equity and return on assets have been used to measure the bank performance. It is found that there is a significant gap between actual practices of corporate governance of Vietnamese banks and the international principles, a statistically significant difference in corporate governance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Credit risks are arising with respect to the debtors are fails to repay the borrowed amount as per the credit contract with the concern financial institutions. This situation may occur due to late repayment, non-payment of full loan balance and non-repayment of interest and principal due to financial loss in the business enterprises etc (Tu et al, 2014). There is positive relationship between success of the project and the credit loss management expense (Pyle, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Credit risks are arising with respect to the debtors are fails to repay the borrowed amount as per the credit contract with the concern financial institutions. This situation may occur due to late repayment, non-payment of full loan balance and non-repayment of interest and principal due to financial loss in the business enterprises etc (Tu et al, 2014). There is positive relationship between success of the project and the credit loss management expense (Pyle, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lack of awareness of the necessary of a corporate governance framework is one critical reason for its weaknesses. There is also a significant gap between the corporate governance practice in Vietnam banking system and international principal (Tu, Son, & Khanh, 2014). Tu et al (2014) also found corporate governance practice in banking that the supervisory board and board of directors is the weakest part using the corporate governance index (CGI).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is also a significant gap between the corporate governance practice in Vietnam banking system and international principal (Tu, Son, & Khanh, 2014). Tu et al (2014) also found corporate governance practice in banking that the supervisory board and board of directors is the weakest part using the corporate governance index (CGI). They also stated that the corporate governance has positive impact on the performance of Vietnam banking system.…”
Section: Literature Reviewmentioning
confidence: 99%